2015
DOI: 10.1093/infdis/jiv216
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Changes at the Glycoprotein Editing Site Associated With Serial Passage of Sudan Virus

Abstract: Sudan virus (SUDV), like the closely related Ebola virus (EBOV), is a filovirus that causes severe hemorrhagic disease. They both contain an RNA editing site in the glycoprotein gene that controls expression of soluble and full-length protein. We tested the consequences of cell culture passage on the genome sequence at the SUDV editing site locus and determined whether this affected virulence. Passage resulted in expansion of the SUDV editing site, similar to that observed with EBOV. We compared viruses posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 29 publications
(57 reference statements)
1
30
0
Order By: Relevance
“…Contaminating DNA was digested with the RNase-free DNase set (Qiagen). RNA samples were prepared for sequencing as previously described (66). Briefly, DNA, rRNA, and mRNA were removed from harvested nucleic acids by using a Turbo DNA-free kit (Life Technologies), a Ribo-Zero magnetic gold kit (Epicenter Biotechnologies), and RNA purification beads (Illumina), respectively.…”
Section: Construction Of Infectious Proviruses and Generation Of Virumentioning
confidence: 99%
“…Contaminating DNA was digested with the RNase-free DNase set (Qiagen). RNA samples were prepared for sequencing as previously described (66). Briefly, DNA, rRNA, and mRNA were removed from harvested nucleic acids by using a Turbo DNA-free kit (Life Technologies), a Ribo-Zero magnetic gold kit (Epicenter Biotechnologies), and RNA purification beads (Illumina), respectively.…”
Section: Construction Of Infectious Proviruses and Generation Of Virumentioning
confidence: 99%
“…However, some historical studies have been performed with viruses of uncertain provenance (e.g., unknown passage history). This is important because it is known that amplification of other filoviruses, including EBOV and Sudan virus (SUDV), results in genetic changes that impact pathogenesis in animal models ( 11 13 ). However, the effect of amplification of MARV on pathogenesis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of amplification of MARV on pathogenesis is unknown. Furthermore, one of the more notable changes found after cell culture passage of EBOV and SUDV occurs at the glycoprotein (GP) RNA editing site ( 11 , 12 ). However, MARV does not contain this editing site, so it is difficult to predict how cell culture passages might affect expression of GP in MARV.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been performed for SUDV, there are no published reports comparing the potential difference in pathogenesis between 7U and 8U EBOV in NHPs [ 7 ]. One may anecdotally compare what data are available for NHP experiments that were identified as using either 7U or 8U challenge stocks; however, this type of comparison is difficult due to the lack of sequence data, or viral pedigree, presented for historical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pigs infected with the 8U EBOV also experienced a delay in death [ 6 ]. A comparison experiment between 7U and 8U has not been conducted in NHPs for EBOV, but Alfson et al, compared the two for SUDV and found no differences [ 7 ]. The two other mutations that arise in the EBOV viral population after passage in vitro were non-synonymous mutations at position 6179 (E47D) in the glycoprotein and at position 10833 (R163K) in VP24.…”
Section: Introductionmentioning
confidence: 99%